2023
DOI: 10.1097/jte.0000000000000291
|View full text |Cite
|
Sign up to set email alerts
|

Predicting First-Time National Physical Therapy Examination Performance for Graduates of an Entry-Level Physical Therapist Education Program

Abstract: Introduction. The National Physical Therapy Examination (NPTE) is a standardized examination designed to assess competence after graduation from an entry-level physical therapist education program. Review of Literature. Previous studies have identified applicant and student variables that are related to NPTE performance, with applicant variables reflecting performance before admission and student variables reflecting performance after admission. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Comparing the performance of our prediction models with those of other studies presents challenges, since in our research, the target variable-self-reported academic performance (ACAD_PERFO)-is subjective, while in most of the others, the target variable is an objective measure like GPA or equivalent ratings [28,[77][78][79][80][81][82][83][84][85][86][87][88][89][90]. We were interested in how students perceived their performance, which is totally different from actual academic achievements.…”
Section: Models Metrics and Comparisonmentioning
confidence: 99%
“…Comparing the performance of our prediction models with those of other studies presents challenges, since in our research, the target variable-self-reported academic performance (ACAD_PERFO)-is subjective, while in most of the others, the target variable is an objective measure like GPA or equivalent ratings [28,[77][78][79][80][81][82][83][84][85][86][87][88][89][90]. We were interested in how students perceived their performance, which is totally different from actual academic achievements.…”
Section: Models Metrics and Comparisonmentioning
confidence: 99%